(untitled) (International Journal of Engineering and Computer Science, 2012)
To secure data or information by a modified RSA cryptosystem based on ‘n’ prime. This is a new technique to provide maximum security for data over the network. It is involved encryption, decryption, and key generation. Prime number used in a modified RSA cryptosystem to provide security over the networks. In this technique we used ‘n’ prime number which is not easily breakable. ‘n’ prime numbers are not easily decompose. This technique provides more efficiency and reliability over the networks. In this paper we are used a modified RSA cryptosystem algorithm to handle ‘n’ prime numbers and provides security.